HUBUNGAN REGULASI DIRI DALAM BELAJAR TERHADAP STRES AKADEMIK MAHASISWA KMPKS YOGYAKARTA - Nurfitriani, Theresia Syarli; Setyandari, Anastasia (SOLUTION, 2022)
The purposes of this research are; 1) to know the level of self-regulated learning on Catholic Students of Southern Sumatra Community in Yogyakarta; 2) to know the level of academic stress of students on Catholic Students of Southern Sumatra Community in Yogyakarta 3) to find out the relationship between self-regulated learning and academic stress at Catholic Students of Southern Sumatra Community in Yogyakarta. This is a descriptive correlation research. The subjects in this study were 50 students from The Catholic Students of Southern Sumatra Community) who were studying in Yogyakarta. Data collection used: 1) The Self-Regulated Learning Questionnaire with 16 valid items and has a Cronbach Alpha reliability index of 0.733; 2) The Academic Stress Questionnaire with 18 valid items and has a Cronbach Alpha reliability index of 0.887. The data analysis technique operated descriptive categorization technique and Pearson Product Moment correlation technique. The results showed that 3 students (6%) had the the highest level of selfregulated learning, 20 students (40%) high, 23 students (46%) moderate, 4 students (8%) low and there were no students (0 %) in the lowest category. Then 1 student (2%) had the highest level of academic stress, 12 students (24%) high, 33 students (66%) moderate, 4 students (8%) low and there were no students in the lowest category. Pearson Product Moment correlation coefficient value is r = -0.389 with ρ =0.005 (ρ0.05). The result indicates that there is a significant negative relationship between self-regulated learning ability and student academic stress.